Tourism-based heritage conservation in Murshidabad: an appraisal. Issue 2 (15th March 2017) - Paul, Subrata Kr.; Roy, Souvanic
ABSTRACT: The article appraises the outcome of promoting tourism as a strategy for heritage conservation in the case of Murshidabad, an archetypal historic town in decline in India. A relational maturity-based framework has been used to examine the complementarities and conflicts between tourism and heritage conservation in the town. The prevailing nature of tourism conservation relationship in Murshidabad upholds the criticality characteristically observed in developing countries, where governments focus primarily on the revenue generating potential of built-heritage centric tourism ignoring the conservation attention necessary to retain authenticity and meaningful existence of historic structures. The overarching issues emerging from the current level of relational maturity in Murshidabad are identified with suggestions for possible policy implications of the study.